STEM-12. DOWNREGULATION OF H-FERRITIN EXPRESSION USING MULTIVALENT CATIONIC LIPOSOMES RESULTS IN INCREASED RADIATION SENSITIVITY IN PATIENT DERIVED GLIOMA INITIATING CELLS. (5th November 2018) - Ravi, Vagisha; Madhankumar, Achuthamangalam; Slagle-Webb, Becky; Connor, James
Abstract: Glioblastoma is the most prevalent and lethal primary brain tumor with a dismal survival rate. The glioma initiating cell (GIC) population within glioblastomas has been associated with treatment resistance and subsequently been implicated in tumor recurrence. Studies from our lab had previously shown that expression of the heavy chain subunit of the iron storage protein ferritin, H-ferritin, is essential for the survival and therapeutic resistance of non-stem glioma cells. Since H-ferritin is overexpressed in GICs, we hypothesized that downregulating its expression in these cells would lead to increased radiosensitivity. We thus developed a novel strategy to sensitize GICs to radiation therapy using a multivalent cationic liposome formulation that could efficiently transfect and deliver H-ferritin siRNA to GICs in vitro . Using patient derived pro-neural T3691 and mesenchymal T387 CD133+ GICs we showed that downregulating H-ferritin led to increased LDH release as well as executioner caspase 3/7 activity in both GIC subtypes. We also found a significant decrease in the levels of Tom 20, a mitochondrial outer membrane protein, indicating reduced mitochondrial mass. However, upon radiation at 8Gy we found that T3691 but not T387 cells showed a significant decrease in cell viability. Upon further investigation we found that knockdown of H-ferritin led to elevated expression of the DNA damage response protein phospho-ϒH2AX to a much higher extent in T387 GICs (9.2 fold) compared to T3691 GICs (3.3 fold) suggesting that these cells might be able to repair DNA damage more efficiently than the pro-neural subtype and thus remain radiation resistant even after H-ferritin loss. Thus, we have demonstrated that loss of H-ferritin in pro-neural GICs leads to increased radiation sensitivity presumably through induction of mitophagy and increased DNA damage. Ongoing studies are focused on further determining the mechanisms through which H-ferritin loss mediates this effect in pro-neural but not mesenchymal GICs.